Dispercity - new development approach for Estonian rural peripheries - Rein Ahas; Neve Albre; Liina Link; Ülar Mark (European Regional Science Association (ERSA), 2001)
Increasing number of people with flexible jobs and mobility and with more free time and resources, would like to spend more time in environment that combines the advantages of urban and rural life. They prefer urban qualities in clean and beautiful environment with full access to information networks, high mobility and advanced social and cultural services. We call this type of new settlement with term "dispersed city". This change in European real estate market is creating new problems how to plan new type of settlement with modern technological standard and how to save nature and local culture from the people who like to move in it. We worked out basic principles and methods for dispersed city - how to integrate qualities of urban and rural environment, information technology and global-local lifestyles with local culture.
Keywords: 330